Tackling functional redundancy of Arabidopsis fatty acid elongase complexes - Batsale, Marguerite; Alonso, Marie; Pascal, Stéphanie; Thoraval, Didier; Haslam, Richard P.; Beaudoin, Frédéric; Domergue, Frédéric; Joubès, Jérôme (Frontiers in Plant Science, 2023)
Very-long-chain fatty acids (VLCFA) are precursors for various lipids with crucial physiological and structural roles in plants. Throughout plant tissues, VLCFA are present in multiple lipid classes essential for membrane homeostasis, and also stored in triacylglycerols. VLCFA and their derivatives are also highly abundant in lipid barriers, such as cuticular waxes in aerial epidermal cells and suberin monomers in roots. VLCFA are produced by the fatty acid elongase (FAE), which is an integral endoplasmic reticulum membrane multi-enzymatic complex consisting of four core enzymes. The 3-ketoacyl-CoA synthase (KCS), which catalyzes the first reaction of the elongation, determines the chain-length substrate specificity of each elongation cycle, whereas the other three enzymes have broad substrate specificities and are shared by all FAE complexes. Consistent with the co-existence of multiple FAE complexes, performing sequential and/or parallel reactions to produce the broad chain-length-range of VLCFA found in plants, twenty-one KCS genes have been identified in the genome of Arabidopsis thaliana. Using CRISPR-Cas9 technology, we established an expression platform to reconstitute the different Arabidopsis FAE complexes in yeast. The VLCFA produced in these yeast strains were analyzed in detail to characterize the substrate specificity of all KCS candidates. Additionally, Arabidopsis candidate proteins were transiently expressed in Nicotiana benthamiana leaves to explore their activity and localization in planta. This work sheds light on the genetic and biochemical redundancy of fatty acid elongation in plants.